PERUBAHAN PARADIGMA PENDIDIKAN ISLAM: APLIKASI ICT DALAM PROSES PEMBELAJARAN PAI DI SEKOLAH - Ahmad Zainuri (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2017)
The use of ICT as a medium of learning and teaching needed to realize the effectiveness and optimization of learning. But be aware that regardless of the medium used learning principles are upheld. It must be recognized that there are still many teachers who